MR parameter quantification with magnetization‐prepared double echo steady‐state (MP‐DESS). Issue 1 (2nd August 2013) - Stöcker, Tony; Keil, Fabian; Vahedipour, Kaveh; Brenner, Daniel; Pracht, Eberhard; Shah, N. Jon
<x xml:space="preserve">Abstract</x> Purpose The mapping of MR relaxation times and proton density has been the subject of research in medical imaging for many years, as it offers the possibility for longitudinal investigation of disease and the correlation with related biochemical processes. The purpose of this study is to provide a fast mapping protocol, which simultaneously acquires MR relaxation times and relative proton density without compromising accuracy and precision. Methods This work presents a novel magnetization‐prepared double echo steady‐state (MP‐DESS) sequence, which was designed to be sensitive to parameter variations of interest, and insensitive to variations of confounding variables. It provides high sensitivity against variations of the MR relaxation times, high acquisition efficiency, and it is insensitive to off‐resonance. Accurate phase graph modeling of the MP‐DESS signal is used to obtain unbiased parameter estimates. Results The approach is validated in phantom and in vivo measurements. A whole‐brain acquisition of 1.4‐mm isotropic resolution was acquired in 15 min. Comparisons to gold‐standard methods suggest a mapping precision of 5% for T1 and M0, and below 10% for T2. Conclusion A new quantitative imaging technique is introduced that allows fast and isotropic simultaneous MR parameter mapping of T1, T2, and M0. Magn Reson Med 72:103–111, 2014. © 2013 Wiley Periodicals, Inc.